2x^2+x-3=0
or,2x^2-2x+3x-3=0
or,2x(x-1)+3(x-1)=0
or,(x-1)(2x+3)=0
Therefore,either x-1=0 or 2x+3=0
If x-1=0,then x=1
If 2x+3=0,then x= -3/2
x=1 or -3/2 ans
2007-08-27 09:40:58
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
I used the completing the square method for this, it never fails.
first step is to divide out 2:
x^2 + (1/2)x = 3/2
second step is to complete the square
x^2 + (1/4)^2x = 3/2 + 1/16
(x + 1/4)^2 = 25/16
Third take the Sqrt of both sides
x + 1/4 = +/- 5/4
fourth solve for x
x = -(1/4) + 5/4
or
x = -(1/4) - 5/4
so
x = -3/2
x = 1
If your answer can not be a negative number then x = 1 would be your answer.
Note: Completing the square can be difficult so using the quadratic equation maybe better.
2007-08-27 10:00:39
·
answer #2
·
answered by Xash 3
·
0⤊
0⤋
Factor by grouping:
(2x + 3)(x - 1) = 2x^2 + x - 3 = 0
Set 2x + 3 = 0; x - 1 = 0
x=0 & x = -3/2
2007-08-27 09:40:58
·
answer #3
·
answered by SoulDawg 4 UGA 6
·
0⤊
0⤋
Factor it
(2x + 3)(x - 1) = 0
let each factor = 0
x-1=0, so x=1
2x + 3 = 0, so 2x = -3, and x = -3/2
Now if your domain is only integers, or whole numbers, the fraction would be negated, and 1 would be the only answer.
2007-08-27 09:41:44
·
answer #4
·
answered by mom 7
·
0⤊
0⤋
Factor it:
(2x + 3)(x - 1) = 0, so x = 1, and x = -3/2
Now test these:
2*1 + 1 - 3 = 0 -- ok
2* (3/2)^2 - 3/2 - 3 = 2*9/4 - 3/2 - 3 = 6/2 - 3 = 0 -- ok
2007-08-27 09:39:14
·
answer #5
·
answered by John V 6
·
0⤊
0⤋
2(x^2) +x -3=0
u need to factorize "x" (middle term) into two terms such that product of the terms is 2(x^2)*(-3)=-6(x^2) and the sum of both the terms should be x...
so, we can do it like this
=> 2(x^2) -2x +3x -3 =0
take common terms outside
=> 2x(x-1) +3(x-1)=0
=> (2x+3)(x-1)=0 [ because (x-1) is common in both the brackets]
now , equating both product terms to zero separately we get,
2x+3 =0 and x-1=0
this gives
x=1 and x=(-3/2)
2007-08-27 09:50:42
·
answer #6
·
answered by just_solved 2
·
0⤊
0⤋
You could solve this either by factoring or by using the quadratic formula. Factoring gives:
(x -1)(2x +3) = 0; so x = 1, or x = -3/2
Using the quadratic formula is harder to depict in text, but you should get the same answer as above.
2007-08-27 09:43:04
·
answer #7
·
answered by Bryan H 2
·
0⤊
0⤋
2x^2 + x - 3 = 0
fill in the brackets
(2x + 3)(x - 1) = 0
either 2x + 3 = 0, if so, x = - 3/2
or x - 1 = 0, if so x = +1
2007-08-27 09:40:03
·
answer #8
·
answered by rosie recipe 7
·
0⤊
0⤋
Use the quadratic formula.
ax^2 + bx +c = 0
(-b +/- sqrt(b^2 - 4ac))/2a
In your equation,
a = 2
b = 1
c = -3
Now substitute.
x = (-1 +/- sqrt(1 - 4*2*-3))/4
x = (-1 +/- sqrt(25))/4
x = (-1 +/- 5)/4
x = 1, 6/4
Now substitute those values back into the equation to determine which works, or if both work.
2(1)^2 + 1 - 3 = 0, true
1 works.
2(6/4)^2 + (6/4) - 3 = 0, false
x = 1
2007-08-27 09:37:51
·
answer #9
·
answered by Matiego 3
·
0⤊
0⤋
2x^2 + x - 3 = 0
a = 2
b = 1
c = -3
x = (-b +/- sqrt(b^2 - 4ac))/(2a)
x = (-1 +/- sqrt(1 + 24))/4
x = (-1 +/- 5)/4 = -3/2 or 1
2007-08-27 09:41:34
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋